New record of Nyctinomops aurispinosus with an update of its known distribution - Portugal-Zegarra, Gandhy; Flores-Quispe, Marisel; Calizaya-Mamani, Giüseppy; Aragón Alvarado, Giovanni (Therya Notes, 2020)
Nyctinomops aurispinosus is one of four species of the genus Nyctinomops (Molossidae) and is considered monotypic. This insectivorous species has a wide but poorly known neotropical distribution. This study documents the first record of the species for the Sama Valley, Tacna department, Perú. In addition, a current distribution map of the species is presented together with facts concerning its dietary composition. The specimen was collected using mist nets during a local bat study and compared with N. aurispinosus individuals in the scientific collection of the Museo de Historia Natural Javier Prado, Universidad Nacional Mayor de San Marcos. The distribution map was made of published records and the diet of the specimen was analyzed by stereoscopy of the contents of its digestive tract. The collected specimen was identified as an adult male N. aurispinosus in reproductive condition. Analysis of the digestive tract contents showed that its diet was composed of lepidopterans. The current distribution map of the species consisted of a total of 78 published records. This new record for Tacna department expands the distribution of N. aurispinosus ca. 270 km to the south of Camaná, Arequipa department, becoming the southernmost record for the Pacific coast. The lepidopteran remains in the digestive tract show that its diet is similar to those reported for other molossids. This finding extends the known distribution of this species to the southwest of South America and increases to ten the number of bat species known from Tacna department. The proximity of this Peruvian record to Chilean territory and regional habitat continuity suggests the probable presence of N. aurispinosus in that country.